Reflexive representations: an artistic exploration of some archaeological theory - Russell, Ian; Cochrane, Andrew (Trinity College Dublin. Long Room Hub, 2006)
These exhibitions seek to contest traditional mechanisms for representation and spectatorship by questioning the status that the document and pictorial image play in archaeological discourse. Photomosaics of iconic archaeologists and archaeological monuments are constructed through the manufacture of archives of public images available over internet search engines. By juxtaposing the figures of archaeologists or archaeological artefacts with a collage of public images, the pieces reveal the manufacture of representations of archaeological identities (archaeologists) and that of the artefacts and monuments with which they work.
Exhibited at 'Unlocking the Treasures', a colloquium and poster exhibition to mark the launch of the Long Room Hub on June 14th 2006
Keywords: Archaeology; Art